Androgen Receptor in Laryngeal Carcinoma: Could There Be an Androgen-Refractory Tumor?. (29th November 2011) - Goulioumis, Anastasios K.; Varakis, John; Goumas, Panos; Papadaki, Helen
Abstract : Androgen receptors (ARs) which are implicated in the pathogenesis of several malignancies can also be a possible downstream effector in laryngeal cancer. In the present study, 97 invasive squamous laryngeal carcinomas were studied by immunohistochemistry for protein expression of AR. Androgen receptors were expressed in 52.6% of tumor specimens, suggesting their implication in the pathogenesis of this tumor. Our study's aim was to investigate the hypothetical scenario of an androgen refractory laryngeal carcinoma where androgen receptors can be activated by nodal molecules in the course of an Epithelial-to-mesenchymal transition (EMT) phenomenon. In line with this we correlated AR expression with the expression of ILK, p-Akt, E-cadherin, β -catenin in our sample as well as with tumor grade and TNM stage. A reverse correlation between nuclear AR and cytoplasmic ILK expression was evidenced, indicating an interaction of those molecules in laryngeal carcinoma. Finally in our material, in those carcinomas that were expressing ARs, stronger nuclear expression of the receptor was characterized by poorer cell differentiation and correlated with the acquisition of EMT features like E-cadherin loss and β -catenin translocation raising a question whether activated ARs can drive an EMT procedure.